Analysis of tissue inflammatory response, fibroplasia, and foreign body reaction between the polyglactin suture of abdominal aponeurosis in rats and the intraperitoneal implant of polypropylene, polypropylene/polyglecaprone and polyester/porcine collagen meshes - Ribeiro,Waston Gonçalves (2021)
ABSTRACT Purpose To compare tissue inflammatory response, foreign body reaction, fibroplasia, and proportion of type I/III collagen between closure of abdominal wall aponeurosis using polyglactin suture and intraperitoneal implant of polypropylene, polypropylene/polyglecaprone, and polyester/porcine collagen meshes to repair defects in the abdominal wall of rats. Methods Forty Wistar rats were placed in four groups, ten animals each, for the intraperitoneal implant of polypropylene, polypropylene/polyglecaprone, and polyester/porcine collagen meshes or suture with polyglactin (sham) after creation of defect in the abdominal wall. Twenty-one days later, histological analysis was performed after staining with hematoxylin-eosin and picrosirius red. Results The groups with meshes had a higher inflammation score (p < 0.05) and higher number of gigantocytes (p < 0.05) than the sham group, which had a better fibroplasia with a higher proportion of type I/III collagen than the tissue separating meshes (p < 0.05). There were no statistically significant differences between the three groups with meshes. Conclusions The intraperitoneal implant of polypropylene/polyglecaprone and polyester/porcine collagen meshes determined a more intense tissue inflammatory response with exuberant foreign body reaction, immature fibroplasia and low tissue proportion of type I/III collagen compared to suture with polyglactin of abdominal aponeurosis. However, there were no significant differences in relation to the polypropylene mesh group.